KARAKTERISTIK PEGAWAI YANG BERHUBUNGAN DENGAN AKURASI DAN KELENGKAPAN PENGISIAN DOKUMEN REKAM MEDIS DI PUSKESMAS PARDAMEAN KOTA PEMATANGSIANTAR TAHUN 2019 - Elisabeth Dame Manalu; Selamat Ginting; Diana Sinulingga (Jurnal Penelitian Kesmasy, 2019)
The Characteristics of Employees Related to the Accuracy and Completeness of Filling in Medical Record Documents at the Pardamean Health Center, Pematangsiantar City in 2019. Thesis, Department of Public Health, Faculty of Public Health, Health Institute of Deli Husada Deli Tua .(Supervised by: Ns. Selamat Ginting, S.Kep, M.Kes) The quality of medical records at the hospital is one determining factor of the quality of service. The aim of the research was to analyze the relationship between the employment status, knowledge, motivation, expertise, and the duration of work of the physician with the completeness of the medical record datasheet resume during hospitalization. This research was a quantitative research survey analytic approach, with a cross-sectional study design. The population was 55 doctors, the sample in this study was the entire population, data analysis was chi-square, and multiple logistic regressions. The results showed that there was a relationship between employment status and knowledge with the completeness of the medical record data. There was no relationship between motivation and skills with the completeness of the medical record data. There was a relationship between the duration of work with the completeness of the medical record data. This study suggests the development of human resources through education and training, guidance to the physicians on the filling of medical record and document, provide internal training regarding the determination of the main diagnosis in accordance with the ICD-10, improved knowledge of the completeness of filling medical records. Motivating doctors fill medical records through career development, promotion, and providing feedback with reward and punishment.